Production of pacus and tambacus in cage culture in the southern region of the state of são paulo - Leonardo, A. F.; Lattanzi, G. R. [UNESP]; Bueno, G. W. [UNESP]; Baccarin, A. E.; Reis Neto, R. V. [UNESP] (Cordoba University Press (UCOPress), 2020)
The study aimed to evaluate physical and chemical water conditions of a rural reservoir utilized for cage fish culture in Pariquera-Acu, SP. In this place 12 cages of 4 m3 were installed and stocked with 300 pacus e 300 tambacus per 12,5 kg/m3, during the period of 180 days. To determine reservoir water quality five points of collection were analyzed every month: water supply, fish rearing area divided into three depths (10 cm, 70 cm and 150 cm) and effluent. Averages of analyzed parameters ± standard deviation were: dissolved oxygen, 6.83 ± 0.7 mg O2D L-1; maximum and minimum temperature, 27,20 ± 2,08 and 21,38 ± 1,34 ºC, respectively; hydrogenionic potential, 6,45 ± 0,74; transparency, cm; total alkalinity, 19,26 ± 9,40 mg CaCO3 L-1; electric conductivity, 49,38 ± 3,60 μS cm-1; total ammonia, 0,002 ± 0,004 mg L-1, total dissolved phosphorus 0,01 ± 0,01 mg L-1.Calculated Trophic Estate Index was 49,3 ± 7,3 . We conclude that pacus e tambacus cage culture did not compromise the water quality of rural reservoir. However animal production good practices and environmental monitoring should be followed for a sustainable fish culture.
Produção de pacus e tambacus em tanques-rede na região sul do estado de são paulo
Keywords: Limnology; Ponds; Sustainable aquaculture